치위생과 학생들의 학습동기와 학습몰입이 학업성취도에 미치는 영향 - 강용주(Yong-Ju Kang); 박혜민(Hye-Min Park) (한국구강보건과학회지, 2021)
Objectives: The present study aimed to investigate the effects of the learning motivation and commitment of dental hygiene students on their academic achievement. Methods: Descriptive statistics, t-test, ANOVA, Pearson's correlation, and multiple regression were used to analyze the students' learning motivation, learning commitment, and academic achievement. Results: While students’ learning motivation and commitment were positively correlated with academic achievement, the strength of this correlation significantly differed according to their course satisfaction and grade. Conclusions: It is necessary to develop and implement teaching methods and learning strategies that enhance students’ learning motivation and commitment and ultimately improve academic achievement. KCI Citation Count: 3